2021
DOI: 10.1016/j.tranon.2021.101185
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic models for lymph node metastasis prediction in cervical cancer: can we think beyond sentinel lymph node?

Abstract: Liu and colleagues performed a retrospective study to validate a computed tomography (CT) scan-based radiomic model to detect lymph node metastasis in cervical cancer. The proposed model incorporating the arterial and venous phase CT-scan features represented a non-invasive method exhibiting high sensitivity in the prediction of lymph node metastasis. It is well established that lymph node metastasis is one of the most significant prognostic factors in cervical cancer. For this reason, management of cervical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that tumour volume, pelvic lymph node status 36 and concurrent chemotherapy are independent prognostic factors of LACC 3 . But Lucia et al 37 reported that radiomic models have higher prognostic power than clinicopathological parameters, such as FIGO stage, tumour volume and nodal stage.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated that tumour volume, pelvic lymph node status 36 and concurrent chemotherapy are independent prognostic factors of LACC 3 . But Lucia et al 37 reported that radiomic models have higher prognostic power than clinicopathological parameters, such as FIGO stage, tumour volume and nodal stage.…”
Section: Discussionmentioning
confidence: 98%
“…LNM is one of the main causes of poor prognosis in patients with cervical cancer [ 34 , 35 ]. In the early, middle, and advanced stages, the 5-year survival rate of cervical cancer without lymph node metastasis is close to 90%, while the 5-year survival rate drops sharply to 65% in cervical cancer with lymph node metastasis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the potential application of a radiomics model to predict the risk of cervical cancer has been proposed with very interesting results (18,19). The combination of radiomics with clinicopathologic markers may aid in predicting the risk of lymph node metastasis with high accuracy.…”
mentioning
confidence: 99%